Analisis Lambung Pensi (Corbicula sumatrana Clessin) Di Danau Singkarak - Tampubolon, Rostina - (STKIP PGRI Sumbar, 2014)
Singkarak Lake is currently used for various activities, such as fishing, tourism, Hydroelectric Power Plant (HEPP), Shower Wash latrine (toilet) and disposal of household waste. Research on the analysis of stomach Pensi (Corbicula sumatrana Clessin) in Singkarak Lake was conducted in February 2013. From the analysis of natural food in the stomach pensi found Phytoplankton, Detritus and 11 genera. The frequency of the presence of natural food that is pensi size <10 mm was Detritus, Staurastrum and Oscillatoria are 1, pensi size is 10-20 mm and Staurastrum Detritus is 1, and the size of> 20 mm was Detritus, Staurastrum and Oscillatoria is 1. The relative abundance were highest pensi size <10 mm is Staurastrum of 18.33% followed by Oscillatoria and Detritus of 16.67%, the size of 10-20 mm is Detritus 25.39%, followed Staurastrum and Cymbella by 12.69%, and in size> 20 mm is Detritus of 32%, followed by 16% Staurastrum. From the analysis it is known that the main food Corbicula sumatrana Clessin is Detritus and Fitoplanton. .